2007
DOI: 10.1002/adem.200700096
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Recrystallization Behavior of a Directionally Solidified Superalloy

Abstract: Directionally solidified (DS) nickel-base superalloys are widely used for turbine blades in aircraft engines and industrial gas turbines. The surface recrystallization, detrimental to mechanical properties of DS superalloys, is an influencing factor in the engineering failures. [1][2][3][4] For conventional polycrystalline metals, recrystallization is an effective approach to optimizing microstructure and thus to improving mechanical property, such as grain refining and strength improving. Industrially, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Oblak and Owczarski [15] reported this phenomenon in as early as 1968 where they observed recrystallization in cold swaged Udimet-700 alloy when it was annealed at 980 • C. Subsequently, many others have also reported the phenomenon in various equiaxed, DS and single crystal superalloys [1,3,7,8,16]. In general, RX in DS superalloys occurs during heat treatment or long-term service when the starting strained ␥-␥ structure of the superalloy transforms into strain-free equiaxed grains of ␥-␥ .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Oblak and Owczarski [15] reported this phenomenon in as early as 1968 where they observed recrystallization in cold swaged Udimet-700 alloy when it was annealed at 980 • C. Subsequently, many others have also reported the phenomenon in various equiaxed, DS and single crystal superalloys [1,3,7,8,16]. In general, RX in DS superalloys occurs during heat treatment or long-term service when the starting strained ␥-␥ structure of the superalloy transforms into strain-free equiaxed grains of ␥-␥ .…”
Section: Discussionmentioning
confidence: 92%
“…The oxide growth stresses generated during the high temperature exposure (either cyclic or isothermal) might also have a limited contribution to the driving force for the above phase transformation [1,8]. In most previous studies, large prior strains (up to 50%) have been imposed for inducing RX inside a superalloy [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the LSFed nickel based superalloy Inconel 718 was mainly composited of γ-phase matrix in the form of columnar dendrite growing almost in the deposition direction, resulted in the obvious anisotropic structures and mechanical properties [7][8][9]. Owing to the repeated rapid heating and rapid cooling along with the moving of high power laser beam, residual thermal stresses were remained in the LSFed materials, which is beneficial for driving the recrystallization process in subsequent heat treatment.…”
Section: Introductionmentioning
confidence: 99%